Efektivitas Pupuk Anorganik Yang Berbeda Untuk Substtusi Urea Sebagai Sumber Nitrogen Pada Nutrien Kultur Nannochloropsis sp. - Ilyas, Muhammad Ilyasya; Ilyasya, Muhammad; Irawan, Henky; Sinaga, Daniel (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2026)
Nitrogen is one of the nutrients needed by Nannochloropsis sp., but there has been no determination of fertilizer dosage based on fertilizer nitrogen sources. This study aims to determine the provision of inorganic fertilizers capable of substituting urea in the culture nutrients of Nannochloropsis sp. and to find out inorganic fertilizers that are effective for use as a nitrogen source for the Nannochloropsis sp. cell population. This study used a Completely Randomized Design (CRD) with 1 control and 3 treatments, namely: Control (Urea 50 mg / L Urea, Za, TSP, EDTA), treatment A (NPK Fertilizer 16 16 16, Za, TSP, EDTA), treatment B (Calcium Nitrate Fertilizer, ZA, TSP, EDTA), treatment C (Calcium Ammonium Nitrate Fertilizer, ZA, TSP, EDTA), each with 3 replications. The parameters observed included daily density, peak population, doubling time, water quality and light intensity. The results showed that during 7 days of maintenance, the highest daily density of Nannochloropsis sp. cells was found on D-5 of maintenance with the highest growth in treatment C (Calcium Ammonium Nitrate Fertilizer) which was 18,528,611 cells/ml with the fastest doubling time in treatment C (Calcium Ammonium Nitrate Fertilizer) which was 37.04 cells/hour and the lowest growth in treatment A (NPK 16 16 16 Fertilizer) which was 17,128,611 cells/ml with the longest doubling time in the control (Urea Fertilizer) which was 46.6 cells/hour. The peak population for the control and all treatments was found on D-5 of maintenance. The light intensity during the study ranged from 6,357 lux. These results indicate that NPK 16 16 16, Calcium Nitrate and Calcium Ammonium Nitrate fertilizers are able to substitute urea as a nitrogen source in the nutrient culture of Nannochloropsis sp. and the three organic fertilizers are effective in being used as a nitrogen source for the Nannochloropsis sp. cell population.